1998
DOI: 10.2166/wst.1998.0697
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation of sequencing batch reactors for biological phosphorus removal: comparative rRNA sequence analysis and hybridization with oligonucleotide probes

Abstract: Four laboratory-scale sequencing batch reactors (SBRs) were operated to evaluate whether bioaugmentation with Acinetobacter spp. can be used to improve start-up and performance of enhanced biological phosphorus removal (EBPR) systems. Two of the SBRs were bioaugmented during start-up by adding pure cultures of Acinetobacter spp., the third reactor received an amendment of activated sludge from a laboratory-scale EBPR system, and the fourth reactor, receiving no amendment, served as a control. Various chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…This clearly indicated that the more dominant microbial species existed in the flocs system. Meanwhile, β-proteobacterium was widely reported to be responsible for EBPR (Ahn et al 2002;Bond et al 1999;Crocetti et al 2000;Oerther et al 1998). This result implied that the different sludge morphology could influence dominant species and phosphorus removal efficiency in EBPR.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly indicated that the more dominant microbial species existed in the flocs system. Meanwhile, β-proteobacterium was widely reported to be responsible for EBPR (Ahn et al 2002;Bond et al 1999;Crocetti et al 2000;Oerther et al 1998). This result implied that the different sludge morphology could influence dominant species and phosphorus removal efficiency in EBPR.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter spp. have been historically important in the study of activated sludge, especially in the area of enhanced biological phosphorus removal (20). Therefore, this genus was selected for further study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fluorescence in situ hybridization (FISH) has been used to quantify the biomass of specific filamentous microorganisms in activated sludge using a relationship between the number and length of individual target cells and biomass concentration (10). In addition, membrane hybridizations have been used to measure the activity of microbial populations in foaming activated sludge (11) and in activated sludge systems operated for enhanced biological phosphorus removal (20). Although these approaches may not work for all microbial populations-such as metabolically active microorganisms with low rRNA content (19) and metabolically inactive microorganisms with a high residual rRNA content (25,32)-oligonucleotide hybridization probes targeting rRNA have been used successfully to study the microbial ecology of activated sludge (5).…”
mentioning
confidence: 99%
“…Briefly, a first hybridisation using the peroxidase-conjugated probe LGC354A (Meier et al, 1999) for low guanine-cytosine (GC) content Grampositive bacteria was done including the catalysed reporter deposition step, but the hybridised filter pieces were not counterstained with DAPI. Instead, they were incubated for 20 min at room temperature in 0.01M HCl to inactivate the horseradish peroxidase and then a second hybridisation was run using the monolabeled S-G-Acin-0652-a-A-18 probe (Oerther et al, 1998) for Acinetobacter spp. conjugated to Cy3.…”
Section: Double Fluorescence In Situ Hybridisationmentioning
confidence: 99%